How to re-enchant workplaces and organizations? An introduction to the special issue - Inmaculada Beltrán Martín; Alma Ma Rodríguez Sánchez; Despoina Xanthopoulou (BRQ Business Research Quarterly, 2022)
Enchanting work is a polysemic term that can account for multiple interpretations. It can be defined as a feeling of being connected in an affirmative way to existence. In organizational terms, enchanted workplaces are places of wonder that allow people to be active agents, who can impact on their environment, find meaning in their work, and flourish. In this context, enchantment has been operationalized in organizational and managerial literature in a variety of ways, including being resourceful, happy, resilient, passionate, motivated, or healthy at work, among others. The main purpose of this special issue was to highlight those elements that may promote enchanting work environments, and the processes through which (re-)enchantment may be achieved. Also, we were interested in understanding re-enchantment as an internal process.
Keywords: M50; 650; analysis; empowerment; job design/analysis; Leadership theories; multi-level (e.g.; HLM; WABA; RCM); theoretical perspectives